2021
DOI: 10.1002/tox.23336
|View full text |Cite
|
Sign up to set email alerts
|

AMOTL2 restrains transforming growth factor‐β1‐induced proliferation and extracellular matrix deposition of airway smooth muscle cells via the down‐regulation of YAP1 activation

Abstract: Angiomotin‐like 2 (AMOTL2) is a key modulator of signaling transduction and participates in the regulation of various cellular progresses under diverse physiological and pathological conditions. However, whether AMOTL2 participates in asthma pathogenesis has not been fully studied. In the present work, we studied the possible role and mechanism of AMOTL2 in regulating transforming growth factor‐β1 (TGF‐β1)‐induced proliferation and extracellular matrix (ECM) deposition of airway smooth muscle (ASM) cells. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…The dephosphorylation of YAP and TAZ, along with the upregulation of their nuclear localization, resulted in increased proliferation and migration of ASMCs 21,23 . Several recent studies have demonstrated that the deactivation of YAP can reverse the phenotypic switching of ASMCs that is triggered by either transforming growth factor‐β‐ or tumor necrosis factor‐α 24,26,43 . Therefore, it is imperative to ascertain the regulatory mechanism of YAP/TAZ that underlies the phenotypic switching of ASMCs during the process of asthmatic airway remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The dephosphorylation of YAP and TAZ, along with the upregulation of their nuclear localization, resulted in increased proliferation and migration of ASMCs 21,23 . Several recent studies have demonstrated that the deactivation of YAP can reverse the phenotypic switching of ASMCs that is triggered by either transforming growth factor‐β‐ or tumor necrosis factor‐α 24,26,43 . Therefore, it is imperative to ascertain the regulatory mechanism of YAP/TAZ that underlies the phenotypic switching of ASMCs during the process of asthmatic airway remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…21,23 Several recent studies have demonstrated that the deactivation of YAP can reverse the phenotypic switching of ASMCs that is triggered by either transforming growth factor-β-or tumor necrosis factor-α. 24,26,43 Therefore, it is imperative to ascertain the regulatory mechanism of YAP/TAZ that underlies the phenotypic switching of ASMCs during the process of asthmatic airway remodeling. CRSP2 has significant impacts on focal adhesions and cytoskeletons, which in turn affect the activation of YAP/TAZ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 AMOTL2 reduces YAP1 expression to repress TGF-β1-mediated proliferation and ECM generation in ASMCs. 34 Eosinophils facilitate ASMC proliferation and ECM production through upregulating WNT-5a and TGF-β1 in asthma. 35 In this study, we found that JNJ0966 relieved the ECM deposition in PDGF-BB-induced ASMCs.…”
Section: Discussionmentioning
confidence: 99%